2019
DOI: 10.1186/s13756-019-0509-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of class 1, 2 and 3 integrons in clinical multi-drug resistant Klebsiella pneumoniae isolates

Abstract: Background The aim of this study was to characterize class 1,2 and 3 integrons in clinical MDR Klebsiella pneumoniae isolates in Kashan, Iran. Methods One hundred-eighty one Klebsiella pneumoniae were recovered from clinical specimens during November 2013 to October 2014. Antimicrobial susceptibility patterns were determined by disk diffusion method according to the Clinical and Laboratory Standards Institute (CLSI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 33 publications
(48 reference statements)
2
44
1
Order By: Relevance
“…Finally, forty-nine (98%) out of our 50 K. pneumoniae isolates were positive for the intI1 gene. Lower percentages (74%, 69%, and 53%) were reported by Derakhshan et al, Zaki et al, and Liao et al; in contrast, all (100%) isolates of Firoozeh et al in Iran were positive for this gene 7,9,22,25 .…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Finally, forty-nine (98%) out of our 50 K. pneumoniae isolates were positive for the intI1 gene. Lower percentages (74%, 69%, and 53%) were reported by Derakhshan et al, Zaki et al, and Liao et al; in contrast, all (100%) isolates of Firoozeh et al in Iran were positive for this gene 7,9,22,25 .…”
Section: Discussionmentioning
confidence: 66%
“…Nonetheless, Derakhshan et al in Iran and Liao et al in China reported that 1% and 2% of their isolates, respectively, were positive for class 2 integrons 9,25 . In addition, Firoozeh et al in Iran reported that 37% of their isolates were positive for this gene 7 . Similarly, none of our isolates was positive for intI3; this finding matches the results reported by Derakhshan et al, Zaki et al and Firoozeh et al 7,9,22 . Significant correlations were found between the intI1 gene and resistance to aztreonam and ceftriaxone (p-value ≤ 0.05).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Pathogenicity of MDR Klebsiella pneumoniae has been attributed to the possession and production of resistance genes, virulence genes, integrons, production of toxins (Li et al, 2013;Firoozeh et al, 2019). Extended Spectrum Beta-Lactamases genes from isolated resistant Klebsiella pneumoniae include TEM, SHV, and CTX-M.…”
Section: Discussionmentioning
confidence: 99%
“…Five classes of MIs have been described but the class 1 integron is, by far, the most prevalent and clinically relevant. The first multidrug resistance plasmids that were isolated in the 1950s carried class 1 mobile integrons (Liebert et al, 1999;Mitsuhashi et al, 1961;Rownd et al, 1966;Stokes & Hall, 1989), and recent surveys have shown that class 1 integrons are found in a substantial fraction of isolates of E. coli (Halaji et al, 2020;Rao et al, 2006;Yu et al, 2003), K. pneumoniae (Firoozeh et al, 2019;Li et al, 2013), P. aeruginosa (Oliver et al, 2015;Ruiz-Martínez et al, 2011), and A. baumanii (Chen et al, 2015;Turton et al, 2005).…”
Section: Introductionmentioning
confidence: 99%